Logical thinking and its relation with problem Solving among female instructors in the university - لطيف مكي غازي ميسون كريم (College of Education for Women, 2019)
problems with its unobvious effect on scientific creativity and information. Problem solving is one of main goals of researchers because it develops their right logical thinking methods. The present study aims at measuring logical thinking among female it structures in the university mea swing problem solving among them ,identifying statically differences significance in logical thinking among female instructors in the university according to (Specialization Variable), identifying differences significance in problem Solving among female instructions in the university according to ( Specialization Variable) and identifying the Correlation between logical thinking and problem solving among female instructors in the university. The sample consists of the main application sample Consisting of (100) female instructors (50) from Scientific specializations and (50) from human ones that had been chosen randomly. The researcher concludes with aunnber of results as: 1- The individuals of the sample, according to the comparison between arithmetic mean and hypothetical on, have logical thinking and the ability of problem Solving at (o,05) significant level.There are no statistically significant differences on the scale of logical thinking according to specialization variable ( Scientific- human) at (0,05) significant level. 3- There are statistically significant differences on the scale of problem solving according to Specialization variable (Scientific- human ) at (0,05) significant lever. 4- There is a correlation between logical thinking and problem solving which is (0,77) among the female instructors at (0,05) significant level. The researcher reaches at some of recommendations, suggestions and conclusions.